Successful immunomodulation in kidney transplant recipients with cytokine release syndrome after coronavirus disease. Issue 5 (24th June 2022) - Takamoto, Daiji; Sasaki, Hajime; Kataoka, Hiroshi; Kodama, Fumihiro; Higuchi, Haruka; Hirano, Tetsuo; Takada, Yusuke; Harada, Shigeru; Harada, Hiroshi; Tanaka, Hiroshi
Abstract : Introduction: Patients with coronavirus disease, especially solid organ transplant recipients, are more susceptible to developing cytokine release syndrome than those with other viral infections. However, currently, treatment methods for such patients have not been established. Here, we describe two cases of successful immunomodulation in Japanese kidney transplant recipients with cytokine release syndrome following coronavirus disease. Case presentation: Two patients who had been receiving long‐term immunosuppressant therapy developed coronavirus disease‐associated pneumonia caused by cytokine release syndrome, following immunosuppressant dosage reduction. However, they recovered immediately after administration of tocilizumab with or without dexamethasone. Conclusion: The immunosuppressant dosage should be reduced to restore host immunity; however, immunomodulation should be considered in cases of suspected cytokine release syndrome.